2020
DOI: 10.1136/jitc-2020-001278
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anti-NY-ESO-1-specific T cells and expression of differential biomarkers in a patient with metastatic gastric cancer benefiting from combined radioimmunotherapy treatment: a case report

Abstract: Combined radioimmunotherapy is currently being investigated to treat patients with cancer. Anti-programmed cell death-1 (PD-1) immunotherapy offers the prospect of long-term disease control in solid tumors. Radiotherapy has the ability to promote immunogenic cell death leading to the release of tumor antigens, increasing infiltration and activation of T cells. New York esophageal squamous cell carcinoma-1 (NY-ESO-1) is a cancer–testis antigen expressed in 20% of advanced gastric cancers and known to induce hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It is a highly immunogenic tumor-specific antigen inducing both humoral and T cell responses and it is considered as an attractive target for immunotherapy. In fact, NY-ESO-1 can be considered as a dynamic biomarker and a potential target of immunotherapy ( 4 ). Indeed, it has been demonstrated that melanoma patients treated with ipilimumab had an increased rate of NY-ESO-1-specific immunity that was associated with improved clinical benefit of the treatment, especially in patients developing both NY-ESO-1-specific antibody and specific CD8+ T cells ( 5 ).…”
Section: Monitoring Specific Anti-tumor Immune Responses To Tumor Associated Antigens And/or Neoantigens Before and During Immune Checkpomentioning
confidence: 99%
See 3 more Smart Citations
“…It is a highly immunogenic tumor-specific antigen inducing both humoral and T cell responses and it is considered as an attractive target for immunotherapy. In fact, NY-ESO-1 can be considered as a dynamic biomarker and a potential target of immunotherapy ( 4 ). Indeed, it has been demonstrated that melanoma patients treated with ipilimumab had an increased rate of NY-ESO-1-specific immunity that was associated with improved clinical benefit of the treatment, especially in patients developing both NY-ESO-1-specific antibody and specific CD8+ T cells ( 5 ).…”
Section: Monitoring Specific Anti-tumor Immune Responses To Tumor Associated Antigens And/or Neoantigens Before and During Immune Checkpomentioning
confidence: 99%
“…Our results showed that NY-ESO-1-specific T cells response was increased after the fifth cycles of treatment (stable disease) but had a significant decline at progression, and that PD-1+ T cells population was markedly reduced after anti-PD-1 treatment ( 6 ). Recently, we have characterized a dynamic NY-ESO-1- specific T cells population that was significantly increased at treatment response in a patient with a metastatic gastric cancer who displayed a long-lasting response to combined radio-immunotherapy ( 4 ).…”
Section: Monitoring Specific Anti-tumor Immune Responses To Tumor Associated Antigens And/or Neoantigens Before and During Immune Checkpomentioning
confidence: 99%
See 2 more Smart Citations
“…Radioimmunotherapy is also currently being investigated, with radiotherapy having been shown to modulate the immune microenvironment of the tumor and upregulate the expression of PD-L1 on tumor and immune cells to treat patients with cancer (51). In a case report of one patient, radiotherapy combined with pembrolizumab was able to provide a disease control condition (with no further therapy) for a period of 12 months before relapse (52), implying that radioimmunotherapy may have potential in combination therapy. Various combined treatment methods for advanced recurrent or metastatic gastric cancer are being actively explored, and positive results may provide options for the perioperative period.…”
Section: Current Status Of Immunotherapy In Gastric Cancermentioning
confidence: 99%